Using Six Sigma DMAIC Cycle to Improve Workplace Safety in the Company from Automotive Branch: A Case Study - Knop, Krzysztof (Manufacturing Technology Journal, 2022)
The article presents the results of the use Six Sigma DMAIC cycle to improve workplace safety and decrease the cost associated with work accidents in the company from the automotive branch. Selected tools of the DMAIC cycle were used at each stage: the project card and the Pareto-Lorenz diagram at the define (D) stage, the matrix diagram at the measure (M) stage, the Ishikawa diagram with the verification of causes at the analysis (A) stage, the 5WHY method at the improve (I) stage and the c control chart at the control (C) stage. Each of the successive stages was based on the results of the previous one in order to achieve a lasting solution for the analysed problem by the implementation of remedial measures. Because of the implementation of remedial measures, the level of work safety in the examined company was improved. The DMAIC analysis made it possible to identify the main causes (Xn) of accidents at work and to objectively evaluate them in order to discover the root cause (Xn!) of the problem. The root cause turned out to be inadequate protection of the lathe due to the protective cover installed too far away from the lathe chuck, which resulted in the catching of protective sleeves or gloves of the lathe operators and accident events in the form of upper limb damage. The solution to this problem was to reduce the gap between the guard and the lathe chuck by adjusting the guard so that no more items of workers' clothing were caught while the machine was running. The article proves the effectiveness of using the Six Sigma DMAIC cycle in analyzing and improving the state of occupational safety and is an incentive to use this cycle and a specific set of tools to analyze similar problems.
Keywords: Quality management; Work safety management; Risk management; Six Sigma; DMAIC; Improvement